Between Vocabulary and Digital Media: To what Extent the Implementation of TikTok in EFL Classroom Setting - Mitsela Arunde; Yapi Wongkar; Awaludin Rizal (English Education Department, 2025)
The purpose of this research is to determine whether TikTok can improve students vocabulary mastery With the rise of social media as an innovative educational resource TikTok s engaging video format presents a unique opportunity for language learning This is a quantitative study using pre test and post test design through written test in a form of Multiple Choice fill in the blank Mix and Match question and questionnaire The subjects of this study consisted of 18 students from Class 10 at SMA Negeri 1 Tatoareng The highest score on the pre test was 50 while the lowest score was 20 In contrast the post test results showed a remarkable improvement with the highest score reaching 100 and the lowest score being 80 while the mean score for the pre test was 40 and the mean score for the post test go up till to 85 These results indicate significant improvements leading to the conclusion that TikTok is an effective learning medium for enhancing English vocabulary mastery among students at SMA N 1 Tatoareng < p>